Amino Acid Mutation in Position 349 of Glycoprotein Affect the Pathogenicity of Rabies Virus - Luo, Jun; Zhang, Boyue; Wu, Yuting; Guo, Xiaofeng (Frontiers in Microbiology, 2020)
Rabies, caused by rabies virus (RABV), is a zoonotic disease infecting mammals including humans. Studies have confirmed that glycoprotein (G) is most related to RABV pathogenicity. In the present study, to discover more amino acid sites related to viral pathogenicity, artificial mutants have been constructed in G of virulent strain GD-SH-01 backbone. Results showed that pathogenicity of GD-SH-01 significantly decreased when Gly349 was replaced by Glu349 through in vivo assays. Gly349→Glu349 of G did not significantly influence viral growth and spread in NA cells. Gly349→Glu349 of G increased the immunogenicity of GD-SH-01 in periphery and induced more expression of IFN-α in brain in mice. It was observed that Gly349→Glu349 of G led to enhanced blood-brain barrier permeability at days 5 post infection. All together, these data revealed that Gly349→Glu349 of G mutation decreased RABV pathogenicity through enhanced immune response and increased blood-brain barrier permeability. This study provides a new referenced site G349 that could attenuate pathogenicity of RABV.